Respuesta :
[tex]\huge{\boxed{5}}[/tex]
The Pythagorean theorum states that when [tex]a[/tex] and [tex]b[/tex] are sides and [tex]c[/tex] is the hypotenuse, [tex]a^2 + b^2 = c^2[/tex]
So, let's plug in the values. [tex]3^2 + b^2 = (\sqrt{34})^2[/tex]
Simplify. The square of a square root is the number inside the square root. [tex]9 + b^2 = 34[/tex]
Subtract 9 from both sides. [tex]b^2 = 25[/tex]
Get the square root of both sides. [tex]\sqrt{b^2} = \sqrt{25}[/tex]
[tex]b=\boxed{5}[/tex]
Answer:
5
Step-by-step explanation:
Use the Pythagorean theorem:
[tex]leg^2+leg^2=hypotenuse^2[/tex]
We have
[tex]leg=3,\ hypotenuse=\sqrt{34}[/tex]
Let's mark the other leg as x.
Substitute:
[tex]3^2+x^2=(\sqrt{34})^2[/tex] use (√a)² = a
[tex]9+x^2=34[/tex] subtract 9 from both sides
[tex]x^2=25\to x=\sqrt{25}\\\\x=5[/tex]